Arabidopsis Tetraspanins Facilitate Virus Infection via Membrane-Recognition GCCK/RP Motif and Cysteine Residues - Zhu, Tingyu; Sun, Yanbiao; Chen, Xu (Frontiers in Plant Science, 2022)
Tetraspanins (TETs) function as key molecular scaffolds for surface signal recognition and transduction via the assembly of tetraspanin-enriched microdomains. TETs’ function in mammalian has been intensively investigated for the organization of multimolecular membrane complexes, regulation of cell migration and cellular adhesion, whereas plant TET studies lag far behind. Animal and plant TETs share similar topologies, despite the hallmark of “CCG” in the large extracellular loop of animal TETs, plant TETs contain a plant specific GCCK/RP motif and more conserved cysteine residues. Here, we showed that the GCCK/RP motif is responsible for TET protein association with the plasma membrane. Moreover, the conserved cysteine residues located within or neighboring the GCCK/RP motif are both crucial for TET anchoring to membrane. During virus infection, the intact TET3 protein enhanced but GCCK/RP motif or cysteine residues-deficient TET3 variants abolished the cell-to-cell movement capability of virus. This study provides cellular evidence that the GCCK/RP motif and the conserved cysteine residues are the primary determinants for the distribution and function of TET proteins in Arabidopsis.